FAKTOR EKSTERNAL PENYEBAB TERJADINYA KARIES GIGI PADA ANAK PRA SEKOLAH DI PAUD STROWBERRY RW 03 KELURAHAN BANGETAYU WETAN KOTA SEMARANG TAHUN 2016 - Miftakhun N.F; Salikun Salikun; Lanny Sunarjo; Erni Mardiati (Jurnal Kesehatan Gigi, 2016)
TITLEExternal factors associated with causative of dental caries in pre-school children in PAUD Strowberry RW 03, Bangetayu Wetan, Semarang City in 2016ABSTRACTDental Caries is a disease that attacks the dental tissue by damaging the tissue starts from the tooth surface and spread to pulp. Some external factor provokes dental caries are the environment, behaviour, heath care and heredity. 71% preschoolers at PAUD Strowberry have dental karies. This research is to understand the factor that causes dental caries towards preschoolers at PAUD Strowberry.This research uses quantities descriptive with cross sectional to write the essay. Using totalsampling method for searching the sample includes the sum of the preschoolers at PAUD Strowberry that are infected by dental caries. There are 34 preschoolers that have dental caries. Using questionnaire method to the preschooler’s parents to gather the information for the research we need. The validation and the reliability of the information from the questionnaire has been testedby 20 of the preschooler’s parents at PAUD KasihIbu RW 02. The method to analysis the information using Odds ratio.The result showed the ignorance about dental caries is 76%, bad attitude while brushing teeth is 65%, bad action about causes dental caries is 76%, unhealthy environments for the family is 62%, the ignorance of health care about curing is 68%, and unhealthty heredity about dental caries is 65%. It can be concluded from this research is the knowledge of the disease it the main element that cause dental caries towards preschoolers at PAUD Strowberry. So, the parents should take care therekids teethby brushing their teeth twice a day. Key words : Dental Caries, External Factors, Children